Oxygen-Sufficient Nanoplatform for Chemo-Sonodynamic Therapy of Hypoxic Tumors - Huang, Biying; Chen, Sijie; Pei, Wenjing; Xu, Yan; Jiang, Zichao; Niu, Chengcheng; Wang, Long (Frontiers in Chemistry, 2020)
Modulation of hypoxia is an essential factor for enhancing the effects of antitumor therapies, especially sonodynamic therapy and chemotherapy. To improve the efficacy of combination therapy by reversing the hypoxic tumor microenvironment, we developed shell-core structured PPID-NPs, which were designed with a polymer shell onto the sonosensitizer and a chemotherapeutic drug were loaded and a perfluorocarbon core loaded with oxygen. The perfluorocarbon core provides sufﬁcient oxygen not only for causing the sonosensitizer to produce more singlet oxygen to induce cell apoptosis but also for reducing drug resistance to enhance therapeutic efficacy. Furthermore, the release of chemotherapeutic drugs at the tumor site can be controlled. Thus, PPID-NPs can efficiently inhibit the growth of breast cancer by synergistic therapy under ultrasound exposure. We believe that our oxygen-sufficient nanoplatform could be an ideal therapeutic system for hypoxic tumors.